Hydrolysis product of Nigella A obtained from Nigella glandulifera Freyn seeds promotes apoptosis and AMPK-mediated autophagy in human colon cancer SW620 cells - Chen, Lili; Han, Haote; Amin, Awais; Zhang, Lin; Ma, Shenglin (Archives of Biological Sciences, 2018)
Paper description: Nigella B (NB) is the hydrolysis product of Nigella A (NA) which is extracted from the seeds of Nigella glandulifera Freyn and has been reported to possess several beneficial characteristics, including an anticancer effect. This work demonstrates for the first time the anticancer effect of NA and the mechanism of NB on inducing autophagy in combination with the apoptotic pathway, in human colon cancer cell lines. Our study reveals an anticancer function for NA and NB in colon cancer and supports the use of NA as an antitumor pro-drug and NB as a novel therapeutic drug. Abstract: Nigella B (NB) is the hydrolysis product of Nigella A (NA), which is extracted from the seeds of Nigella glandulifera Freyn. NB has several beneficial characteristics, including antiproliferative activity against several cancer cell lines. In this study, we analyzed the in vitro and in vivo anticancer activity of both NA and NB as well as the potential molecular mechanisms behind the actions of NB. We found that NB treatment led to autophagy and soft apoptosis in colon cancer cells (SW620). NA treatment had no effect on either. Further study showed that NB treatment in SW620 cells led to inhibited phosphorylated mammalian target of rapamycin (p-mTOR) expression but increased phosphorylated-5’ adenosine monophosphate protein kinase (AMPK) expression, a key regulator of autophagy. This suggests that the AMPK-mTOR pathway plays a crucial role in autophagy induction. Separate in vivo studies using NA (40 mg/kg, intragastric administration (i.g.)) and NB (40 mg/kg, i.g.) resulted in inhibited tumor growth in nude mice by 42.82% and 37.20% respectively, when compared with vehicle-administered animals. In vitro tumor protein expression was consistent with its expression in vitro. Taken together, our results reveal an anticancer function for NA and NB in colon cancer and support the use of NA as an antitumor prodrug, and NB as a novel therapeutic drug. https://doi.org/10.2298/ABS171108021C Received: November 8, 2017; Revised: March 30, 2018; Accepted: March 30, 2018; Published online: May 15, 2018 How to cite this article: Chen L, Han H, Amin A, Zhang L, Ma S. Hydrolysis product of Nigella A obtained from Nigella glandulifera Freyn seeds promotes apoptosis and AMPK-mediated autophagy in human colon cancer SW620 cells. Arch Biol Sci. 2018;70(4):603-12.